'I'm not a children and families social worker'. Three mothers' experiences of their children being accommodated under s.25 of the Children (Scotland) Act 1995 - Dawn Simpson (Scottish Journal of Residential Child Care)
This qualitative research study used semi-structured interviews to question three mothers about their experience of the use of s.25 of the Children (Scotland) Act 1995 to place their children in care. S.25 is Scotland's non-statutory approach to accommodating children. National and international research has highlighted that the most common entry into care is without a statutory order. Whilst this is often referred to as voluntary care, research in England and other countries has highlighted that parents have not experienced this process as truly voluntary. This was reflected within the findings of the research. Participants' interviews were emotionally charged and give profound insights into the difficulties of such circumstances that would be valuable for professionals involved to consider. The research highlights the value of a rights-based approach when working in partnership with parents, promoting the use of advocacy and legal support, assessing parents' capacity to understand s.25, providing written and spoken support, and viewing s.25 as an ongoing discussion, not a single event.